Evaluation of limited-sampling strategies to calculate AUC(0–24) and the role of CYP3A5 in Chilean pediatric kidney recipients using extended-release tacrolimus - Galvez, Carla; Boza, Pía; González, Mariluz; Hormazabal, Catalina; Encina, Marlene; Azócar, Manuel; Castañeda, Luis E.; Rojo, Angélica; Ceballos, María Luisa; Krall, Paola (Frontiers in Pharmacology, 2023)
Background. Kidney transplantation (KTx) requires immunosuppressive drugs such as Tacrolimus (TAC) which is mainly metabolized by CYP3A5. TAC is routinely monitored by trough levels (C0) although it has not shown to be a reliable marker. The area-under-curve (AUC) is a more realistic measure of drug exposure, but sampling is challenging in pediatric patients. Limited-sampling strategies (LSS) have been developed to estimate AUC. Herein, we aimed to determine AUC(0-24) and CYP3A5 genotype in Chilean pediatric kidney recipients using extended-release TAC, to evaluate different LSS-AUC(0-24) formulas and dose requirements. Patients and methods. We analyzed pediatric kidney recipients using different extended-release TAC brands to determine their trapezoidal AUC(0-24) and CYP3A5 genotypes (SNP rs776746). Daily TAC dose (TAC-D mg/kg) and AUC(0-24) normalized by dose were compared between CYP3A5 expressors (*1/*1 and *1/*3) and non-expressors (*3/*3). We evaluated the single and combined timepoints to identify the best LSS-AUC(0-24) model. We compared the performance of this model with two pediatric LSS-AUC(0-24) equations for clinical validation. Results. Fifty-one pharmacokinetic profiles were obtained from kidney recipients (age 13.1±2.9 years). When normalizing AUC(0-24) by TAC-D significant differences were found between CYP3A5 expressors and non-expressors (1701.9 vs. 2718.1 ng*h/mL/mg/kg, p<0.05). C0 had a poor correlation with AUC(0-24) (r2=0.5011). The model which included C0, C1 and C4, showed the best performance to predict LSS-AUC(0-24) (r2=0.8765) and yielded the lowest precision error (7.1+/-6.4%) with the lowest fraction (9.8%) of deviated AUC(0-24), in comparison to other LSS equations . Conclusion. Estimation of LSS-AUC(0-24) with 3 time-points is an advisable and clinically useful option for pediatric kidney recipients, using extended-release TAC to provide better guidance of decisions if toxicity or drug inefficacy is suspected. The equation is valid for the three CYP3A5 genotypes, but depending on the genotype variable dose requirements were observed reinforcing to consider genotyping before KTx. Further multi-centric studies with admixed cohorts are needed to determine the short- and long-term clinical benefits.